First record of Cnephidia serraticornella (Zeller, 1839) in the Iberian Peninsula (Lepidoptera: Pyralidae, Phycitinae) - Manuel Garre; Rosa María Rubio; Juan José Guerrero; John Girdley; Antonio S. Ortiz (SHILAP)
The presence of Cnephidia serraticornella (Zeller, 1839) in the Iberian Peninsula is confirmed through a single specimen collected in El Hondo Natural Park to the south of the Alicante province (Spain). This species was found in the lepidopteran collection of Dr J. A. de la Calle kept at the Department of Zoology in Murcia University.